As distintas percepções sobre o empreendedorismo social - Azevedo, Laercio Prates de (2015)
This dissertation is a literature review with exploratory and descriptive purposes, which aims to compile the different perceptions of the term Social Entrepreneurship, but not propon-being of an epistemological analysis on the topic. The main objectives of this research were: 1) to identify the convergences and divergences in the various perceptions of the Social Entrepre-neurship, from the perspectives: American, European and Brazilian; 2) identify whether Social Entrepreneurship can be considered as a new theoretical trend, or can be understood as a sub-category of an existing theory; 3) identify whether Social Entrepreneurship can be considered as practice of Social Management; 4) identify whether the 'Social Business', proposed by Yunus (2010), can be considered as a completely new type of organization, as the author says. For this research were studied literary works available in the physical environment and elec-tronic database. The main concepts studied in this research were: Entrepreneurship; Social Management; Third Sector; Business Management and Social Entrepreneurship. The conclu-sions reached by this study were: 1-a) the main theoretical convergence is the Social Entrepre-neur ability to apply methods and process typically used in for-profit companies, in business that aimed social value creation; 1-b) the main difference is the different perceptions that the United States, Europe and Brazil have about what is Social Entrepreneurship. In the American perspective, these are private sector organizations operating according to market logic and that somehow generates social value. In the European perspective, closer to the social economy, emphasizes the activities of civil society organizations with public functions. In Brazil empha-sizes market initiatives aimed at reducing poverty and transform the social conditions of mar-ginalized or excluded individuals; 2) Social Entrepreneurship is an activity that incorporates much all the practices, methods and processes of commercial entrepreneurship and, as such, should not be considered as a new theoretical trend, but a subcategory of Entrepreneurship theory. 3) Social Entrepreneurship cannot be considered as a practice of Social Management, being much closer to the commercial entrepreneurship practices; 4) the 'Social Business' pro-posed by Yunus (2010), closely resembled in its modus operandi with the Social Enterprises in Western Europe, thus, not supporting the author's claim.